PHÂN TÍCH THÀNH PHẦN MỘT SỐ MẪU TIỀN CỔ Ở PĂNG TIÊNG (LẠC DƯƠNG, LÂM ĐỒNG) BẰNG KỸ THUẬT HUỲNH QUANG TIA X VÀ CÁC PHƯƠNG PHÁP THỐNG KÊ - Lê, Xuân Hưng (Viện Khảo cổ học, 2022)
This study presents the initial results in analyzing the composition of 29 copper coin samples collected in Pang Tieng village, Lat commune, Lac Duong district by X-ray fluorescence (XRF) analysis, and statistical, data processing methods to provide a new perspective in the study of metal coins in Lam Dong. Correlation statistical operations, clustering, and principal component analysis will help to recognize the compositional features of ancient coins. The results show that the group of Chinese ancient coins has a higher content of Cu and Zn elements than that of Vietnamese coins; The composition of Vietnamese age-old coins is also mixed by many other elements such as Sn, Sb, Pb, Bi. Some samples of ancient coins whose names cannot be read were also initially processed to group and determine origin based on elemental composition.